A class of quasilinear Schrödinger equations with critical or supercritical exponents. (August 2015) - Wang, Youjun
Abstract: We study the existence of nontrivial solutions for the following quasilinear Schrödinger equations − Δ u + V ( x ) u + κ 2 [ Δ ∣ u ∣ 2 ] u = l ( u ), x ∈ R N, where V : R N → R and l ( u ) involves critical or supercritical exponents.